Pengaruh Kompetensi Kewirausahaan terhadap Pertumbuhan Bisnis Pakaian di Tanah Abang era Covid-19 - Louis Utama; ronnie resdianto masman; halim putera siswanto; alicia allessandra (LPPM Universitas Buddhi Dharma, 2023)
Business growth experienced obstacles along with the Covid-19 pandemic that hit Indonesia, where this pandemic had a bad impact on the Indonesian economy. The purpose of this study was to determine the effect of strategic competence, ethical competence, network competence on the growth of small and medium enterprises (SMEs) in the clothing sector in Tanah Abang. The population in this study focused on SME entrepreneurs in the clothing sector. The sample in this study amounted to 59 respondents as owners of clothing SMEs in Tanah Abang, Central Jakarta. Questionnaires were distributed directly to clothing SME owners which took place in June 2022.. This study used a non-probability sampling technique with purposive sampling method. The scale used is the Likert scale, using the Smart Partial Least Square (SPLS) version 3.0 application as a data analysis method. This study shows the results that Strategic Competence has an influence on the growth of the clothing SME business in Tanah Abang, Central Jakarta during the Covid-19 period, ethical competence has no influence on the growth of the clothing SME business in Tanah Abang, Central Jakarta during the Covid-19 period, and The network has an influence on the growth of the clothing SME business in Tanah Abang, Central Jakarta during the Covid-19 period. Keywords:Strategic Competencies, Ethical Competencies, Network Competencies, Business Growth